Taxonomy, distribution patterns and ecological and geographic modelling of Clinotettix ussuriensis Bey-Bienko, 1933 (Orthoptera: Tetrigidae) - Sergeev, Michael G.; Molodtsov, Vladimir V.; Lapteva, Svetlana V.; Storozhenko, Sergey Yu. (Zootaxa, 2025)
Clinotettix Bey-Bienko, 1933 is the small genus similar to Tetrix Latreille, 1802 but easy recognizable from the latter in the shape of a head. Two species of Clinotettex are distributed in the Russian Far East, North-East China, and Korean Peninsula. The type species of this genus is Clinotettix ussuriensis Bey-Bienko, 1933, not Acrydium sibiricum ussurianum Bey-Bienko, 1929 as erroneously considered by some researches. We also confirm that Clinotettix chanbaishanensis Wang, Wang et Ren, 2004 is a junior objective synonym of Clinotettix ussuriensis. The data on distribution of C. ussuriensis are summarized. It is the endemic of the temperate deciduous and mixed forest life subzones of the Far East. Its populations are widely distributed, but look like insular. The species abundance is usually low. Hence, C. ussuriensis can be qualified as an endangered species. In any case, a few populations of C. ussuriensies are protected in several Russian nature reserves (zapovedniks), namely Kedrovaya Pad, Ussuriisky, and Sikhote-Alinsky. The species distribution models based on two different approaches (maximum entropy and multidimensional ellipsoid) generated for the contemporary climatic conditions fit well the distribution of the species known localities, but show there are some areas suitable for the species outside its modern range. The models generated for the future climatic conditions demonstrate possible increase of condition suitability over the whole modern species range. Besides, almost all favorable areas outside the actual species range may remain beneficial for the species as well.